How adolescents decide on bariatric surgery: an interpretative phenomenological analysis. Issue 2 (21st January 2018) - Doyle, J.; Colville, S.; Brown, P.; Christie, D.
Summary: The National Institute of Clinical Excellence states that bariatric surgery may be considered for adolescents with severe obesity in 'exceptional circumstances'. However, it is not clear what is deemed to be exceptional, and there is a lack of long‐term outcomes data or research, which would inform patient selection. This is an in‐depth qualitative study involving five adolescents who had previously undergone bariatric surgery (between 1 and 3 years postoperatively) and four who were being assessed for the treatment. All patients were from one tertiary NHS weight management service offering bariatric surgery to adolescents. Participants were interviewed to explore how young people decide whether bariatric surgery is an appropriate intervention for them. Of the nine adolescents recruited, four were male and five female, aged between 17 and 20 years at the time of interview. Participants who had already undergone surgery did so between the ages of 16 and 18. The data were analysed using interpretative phenomenological analysis, and key themes were identified, such as (i) wanting a different future, (ii) experiences of uncertainty, (iii) managing the dilemmas and (iv) surgery as the last resort. The findings suggest that young people are prepared to accept a surgical solution for obesity despite numerous dilemmas. Young people choose this intervention as a way of 'normalizing' when they perceive there is nothing better available. It is argued that these findings may have implications for the counselling of young people living with overweight and obesity and for government policy.